People get ready : African American and Caribbean cultural exchange - Meehan, Kevin, 1962- (Caribbean studies series (Jackson, Miss.), 2009)
Meehan offers historical and theoretical readings of Caribbean and African American interaction from the 1700s to the present. By analysing travel narratives, histories, creative collaborations, and political exchanges, he traces the development of African American/Caribbean dialogue through the lives and works of four key individuals: historian Arthur Schomburg, writer/archivist Zora Neale Hurston, poet Jayne Cortez, and politician Jean-Bertrand Aristide.